2009
DOI: 10.3810/pgm.2009.11.2081
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Chronic Rhinosinusitis in Adults

Abstract: Chronic rhinosinusitis (CRS) is characterized by mucosal inflammation affecting both the nasal cavity and paranasal sinuses; its causes are potentially numerous, disparate, and frequently overlapping. The more common conditions that are associated with CRS are perennial allergic and nonallergic rhinitis, nasal polyps, and anatomical mechanical obstruction (septum/turbinate issues). Other less common etiologies include inflammation (eg, from superantigens), fungal sinusitis or bacterial sinusitis with or withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 144 publications
0
89
0
Order By: Relevance
“…Likely, these diagnostic interventions were appropriately reserved for those who failed initial management, and these patients may, therefore, represent more severe cases. 14,15 The resulting steep slope of the Kaplan-Meier ESS curve (Figure 2) within the first year after CRS diagnosis may in part be skewed by these stringent diagnosis definitions. While we increased the likelihood that CRS was accurately diagnosed, this action may have resulted in a bias toward a sicker patient population that may not represent the disease burden of CRS in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likely, these diagnostic interventions were appropriately reserved for those who failed initial management, and these patients may, therefore, represent more severe cases. 14,15 The resulting steep slope of the Kaplan-Meier ESS curve (Figure 2) within the first year after CRS diagnosis may in part be skewed by these stringent diagnosis definitions. While we increased the likelihood that CRS was accurately diagnosed, this action may have resulted in a bias toward a sicker patient population that may not represent the disease burden of CRS in general.…”
Section: Discussionmentioning
confidence: 99%
“…CRS is difficult to diagnose by symptoms alone. 14,15 We therefore adopted stringent diagnostic criteria involving radiologic or endoscopic confirmation of CRS, resulting in a sample comprising 2.3% of the original starting population, rather than the 20% with any diagnosis of CRS during the study period. Many patients with CRS may never have the diagnosis confirmed by radiologic or endoscopic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…There are several guidelines where recommendations are made, and these demonstrate consistency with regard to inclusion of oral antibiotics, INCS, and selective use of oral corticosteroids (Table X-1). 7,1138,1139 A recent systematic review demonstrated that INCS, oral antibiotics, and oral corticosteroids were used in 91%, 88%, and 62% of all MMT protocols for a mean of 8 weeks, 23 days, and 18 days, respectively. 1140 While incorporating the best available evidence into a recommendation for AMT, including evidence from this ICAR:RS document, a few key points should be remembered.…”
Section: What Is Amt?mentioning
confidence: 99%
“…The advantage of CT is the possibility of three-dimensional reconstructions [20] . To verify chronic sinusitis, CT of the paranasal sinuses should be performed [21] . The images illustrate mucosal swelling, whereas acute sinusitis additionally shows air-fluid level [21] .…”
Section: Mucous Membranes and Squamous Epitheliummentioning
confidence: 99%